The place and role of the proseution authorities in the system of state power in the CIS countries - Abeuov, Е.Т.; Serikbayeva, S.S.; Shakenov, А.О. (Bulletin of the Karaganda University “Law Series”, 2022)
The purpose of the research is to identify the features of the legal status of the prosecution authorities and the organization of the activities of the prosecution authorities in the republics of the Russian Federation, Azerbaijan, Armenia, Belarus, Kyrgyzstan, Moldova, Tajikistan, Uzbekistan, Ukraine, Turkmenistan and Kazakhstan; to consider the prospects for their further development and improvement; to conduct an objective analysis. The study of the constitutional status of the prosecution authorities of these states and the Republic of Kazakhstan is significant both in historical terms and at the present stage, as these states are broughttogether with the common goals and tasks and they possess mutual historical roots which were carried out in the process of their development and acions. The peculiarity of each state and the special position at the present stage make certain adjustments to the organization and activities of this body. In this regard, from a scientific and practical point of view, a general and specific analysis of the formation and development of the constitutional status of the prosecutor's office of the Republic of Kazakhstan with the CIS countries, thedefinition of its place and role in the system of state power make it possible to effectively use the experience of accusations insolution of complicated issues and the fight against crime in conditions of mutual cooperation. In this case, the particular importance is based on the analysis of problems related to the constitutional and legal status of the most significant law enforcement agencies that ensure the organization and activities of the prosecutor's office in some Commonwealth countries, i.e. the rule of law, unity and strengthening of the rule of law. While its necessity is explained by the process of updating the activities of the prosecutor's office, attempts to introduce democratic principles and standards lead the legislators of new sovereign countries to determine the role of the prosecution authorities in national legal systems and fix their real place among state-legal institutions. Authors' conclusions form directions for the improvement of de-signed project of the new legislation of the prosecutor's office by comparing domestic and foreign legislation in the field of investigated issues.